2004
DOI: 10.1074/jbc.m400724200
|View full text |Cite
|
Sign up to set email alerts
|

Positive and Negative Allosteric Modulators of the Ca2+-sensing Receptor Interact within Overlapping but Not Identical Binding Sites in the Transmembrane Domain

Abstract: A three-dimensional model of the human extracellular Ca 2؉ -sensing receptor (CaSR) has been used to identify specific residues implicated in the recognition of two negative allosteric located in transmembranes (TM) 6 and TM7, in the binding pocket for both calcimimetics and calcilytics, despite important differences observed between each family of compounds. The TMs involved in the recognition of both calcilytics include residues located in TM3 (Arg-680 3.28 , Phe-684 3.32 , and Phe-688 3.36 ). However, our s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
167
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(187 citation statements)
references
References 33 publications
16
167
0
2
Order By: Relevance
“…Elucidation of the long-term effects of allosteric modulators on the protein stability of CaR has important pharmacological and clinical implications. Whereas allosteric modulators potentiate or antagonize CaR activity by binding to plasma membrane-localized mature receptors (12,13,34), the current results strongly suggest that these compounds can bind to immature forms of CaR and affect their stability. Chemical chaperones, including Me 2 SO, glycerol, 4-phenylbutyric acid, and trimethylamine N-oxide, and more specific pharmacological chaperones, including substrate analogs, agonists, and antagonists, have been shown to promote folding of receptors, ion channels, and enzymes (18).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Elucidation of the long-term effects of allosteric modulators on the protein stability of CaR has important pharmacological and clinical implications. Whereas allosteric modulators potentiate or antagonize CaR activity by binding to plasma membrane-localized mature receptors (12,13,34), the current results strongly suggest that these compounds can bind to immature forms of CaR and affect their stability. Chemical chaperones, including Me 2 SO, glycerol, 4-phenylbutyric acid, and trimethylamine N-oxide, and more specific pharmacological chaperones, including substrate analogs, agonists, and antagonists, have been shown to promote folding of receptors, ion channels, and enzymes (18).…”
Section: Discussionmentioning
confidence: 88%
“…Allosteric antagonists, including NPS 2143 and Calhex 231, antagonize the stimulatory effects of Ca 2ϩ and are in clinical trials as a treatment for osteoporosis (11). These allosteric modulators bind CaR within the transmembrane heptahelical domain and either increase (calcimimetics) or decrease (calcilytics) the apparent affinity of CaR for Ca 2ϩ (12,13). CaR undergoes dorfin-mediated ubiquitination and degradation via ERAD (endoplasmic reticulum-associated degradation) during biogenesis (1), but little is known about the quality control checkpoints.…”
mentioning
confidence: 99%
“…Homology modeling, docking analysis and mutagenesis studies have shown that nine conserved amino acid residues in the 7TM of T1R3 are involved in allosteric modulator binding. The corresponding residues have also been found in the 7TM of CaS [60][61][62][63] and mGlu receptors [64][65][66] . This implies that class C GPCRs share a common binding site for allosteric modulators.…”
Section: Tm Allosteric Sitesmentioning
confidence: 94%
“…La phénylalkylamine NPS R-568 et le composé indolique Calindol, appartenant à deux familles chimiques différentes, sont considérées comme des calcimimétiques de classe II (Figure 3). Ces molé-cules organiques de faible poids moléculaire présentent une affinité comparable pour le CaR (~0,1 µM) [18][19][20]. Elles déplacent la courbe dose-réponse du Ca 2+ vers la externe des domaines transmembranaires, faisant face au milieu extracellulaire de la cellule et dans lesquelles viendrait interagir le Calhex 231 ( Figure 4A).…”
Section: Les Composés Calcimimétiques De Synthèseunclassified
“…Parmi les acides aminés impliqués dans la reconnaissance des deux calcilytiques Calhex 231 et NPS 2143, seuls des résidus localisés dans les TM 6 et 7 interviendraient dans la liaison des deux calcimimétiques Calindol et NPS R-568 ( Figure 4B) [20]. Les courbes d'activation du CaR par le Ca 2+ sont normalement décalées vers la gauche en présence de ces calcimimétiques.…”
Section: Le Site De Liaison Des Calcimimétiques De Classe II N'est Paunclassified